Potassium Fertilizer Application Rates for Fertigated Edamame Grown on Low-K Soils - Fitri Alfiyah; Purnamawati, Heni; Purwono; Susila, Anas Dinurrohman (Department of Agronomy and Horticulture, IPB University, 2024)
Edamame, a legume consumed fresh as a vegetable, is highly nutritious, particularly protein-rich, and holds significant economic value. However, its cultivation faces challenges, especially on dry land, due to water scarcity and limited nutrient availability, particularly potassium (K). This study, which investigated the impact of potassium fertilization rate on edamame cultivation, underscores the need for further research. The study utilized a single factor, potassium fertilization rate, arranged in a completely randomized block design. Potassium rates consist of 0% X, 50% X, 100% X, 150% X, and 200% X, where X represents the recommended potassium fertilization rate according to the dry soil test device (DSTD) guidelines. Each treatment was replicated five times. Data were analyzed using ANOVA at a 5% significance level, and any significant effects were further examined using orthogonal polynomial and regression analysis. The results indicated that potassium fertilizer rates did not significantly affect edamame height, pod weight per plot, and marketable yield. However, the study identified the optimal potassium fertilizer rate, which was between 83%X and 119%X, equivalent to 83–119 kg.ha⁻¹ of KCl (50–72 kg.ha⁻¹ of K₂O). This range positively increased total branch yield, productive branches, number of flowers, pod weight per plant, number of pods per plant, and plant dry weight, producing a quadratic response pattern. The study recommends further research to optimize potassium fertilizer doses based on DSTD recommendations, particularly at a low K nutrient status, to maximize marketable yields through fertigation.